Teaching English Using Local Culture Content Short Story - Sanda, Silfi (Journal of English and Education (JEE), 2009)
This paper is mainly about the use of local culture content short story in developing students' English proficiency and some activities that can be employed for this purpose. The local culture exposed in the short story is the traditional woven clothes of Palembang, Songket in term of process and product. The short story used in this topic is Cek Ipah "The Palembang Songket Weaver". This short story is authors' original work telling about everyday live of palembang songket weaver which covers both process and also product of songket. It is presented in intriguing theme in order to make the short story more interesting and has some moral lessons to appriciate. In relating this cultural heritage to ELT, approaches used by Collie and Slater is employed. Some activities employed for this short story are whispering sentences technique designed especially for a rousing students' focus on the short story and to train their listening skill, Kids Inspiration outline completing activity for reading comprehension, Drawing mind activity for reading comprehension, cutting process video discussion activity for speaking skills, and sealing time capsule technique activities for developing students' writing ability. The lesson plan designed is just for the first part of the first short story-just until the time when Cek Ipah would like to show songket Lepus Berekam she had woven to her ever after enemy, Cek Beda, the Zainal Songket quality controller. In this lesson plan two kinds of software use, they are windows photo gallery software and 3GP player for video.